Disability, Race, Class, and Gender in Seventh-day Adventist Health Publications, 1880-1910 - Anderson, Talea (Disability Studies Quarterly, 2023)
This article examines discourses in early Seventh-day Adventist health publications with particular attention to the ways that disability played into discussions of vegetarianism. In the nineteenth to twentieth centuries, the Adventist church was at the forefront of conversations in western countries about the value of a meat-free diet. During this time, Adventist health publications made or echoed a variety of arguments in support of vegetarian eating. Pervasive in these arguments were ableist tropes calculated to show how vegetarianism equated to youth, physical stamina, beauty, and intellectual superiority. This rhetoric effectively used disability to craft a vision of vegetarians as white, upwardly mobile people who conformed to traditional gender roles. Disability thus served to demarcate insiders from outsiders by underlining perceived differences between genders, races, and classes of people.